Zinc Supplementation Inhibits Hepatic Apoptosis in Mice Subjected to a Long-Term Ethanol Exposure - Zhou, Zhanxiang (Exp Biol Med (Maywood), 2008)
Hepatocyte apoptosis has been documented in both clinical and experimental alcoholic liver disease. This study was undertaken to examine the effect of dietary zinc supplementation on hepatic apoptosis in mice subjected to a long-term ethanol exposure. Male adult 129S6 mice fed an ethanol-containing liquid diet for 6 months developed hepatitis, as indicated by neutrophil infiltration and elevation of hepatic keratinocyte chemoattractant (KC) and monocyte chemoattractant protein-1 (MCP-1) levels. Apoptotic cell death was detected in ethanol-exposed mice by a terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay and was confirmed by the increased activities of caspase-3 and -8. Zinc supplementation attenuated alcoholic hepatitis and reduced the number of TUNEL-positive cells in association with inhibition of caspase activities. Ethanol exposure caused oxidative stress, as indicated by reactive oxygen species accumulation, mitochondrial glutathione depletion, and decreased metallothionein levels in the liver, which were suppressed by zinc supplementation. The mRNA levels of tumor necrosis factor (TNF)-α, TNF-R1, FasL, Fas, Fas-associated factor-1, and caspase-3 in the liver were upregulated by ethanol exposure, which were attenuated by zinc supplementation. Zinc supplementation also prevented ethanol-elevated serum and hepatic TNF-α levels and TNF-R1 and Fas proteins in the liver. In conclusion, zinc supplementation prevented hepatocyte apoptosis in mice subjected to long-term ethanol exposure, and the action of zinc is likely through suppression of oxidative stress and death receptor-mediated pathways.